The Blackwell Dictionary of Western Philosophy. - Bunnin, Nicholas (John Wiley & Sons, 2007)
The Blackwell Dictionary of Western Philosophy is a concise reference to the whole history of Western philosophy, from ancient Greece to the present day. The Dictionary's entries are written in a clear and direct style, which makes it easy for readers to engage with the central questions of philosophy, from epistemology to ethics, and from metaphysics to the philosophy of mathematics. The authors pay particular attention to terms that are crucial to contemporary debate. A unique feature of the Dictionary is its use of a quotation to conclude each entry on philosophical terms. These quotations.